1990
DOI: 10.1083/jcb.110.3.789
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal segregation of endothelial cell integrin and nonintegrin extracellular matrix-binding proteins during adhesion events.

Abstract: Abstract. Bovine aortic endothelial cell (BAEC) attachments to laminin, fibronectin, and fibrinogen are inhibited by soluble arginine-glycine-aspartate (RGD)-containing peptides, and YGRGDSP activity is responsive to titration of either soluble peptide or matrix protein. To assess the presence of RGD-dependent receptors, immunoprecipitation and immunoblotting studies were conducted and demonstrated integrin/~1, /33, and associated t~ subunits as well as a/31 precursor. Immunofluorescence of BAECs plated on lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 71 publications
(69 reference statements)
3
43
1
1
Order By: Relevance
“…These events appear to be dependent both on cell-cell and cell-matrix interactions. Previous studies have revealed that interaction of endothelial cells with components of extracellular matrix results in modulation of shape and behavior including cytoskeletal reorganization, cell spreading and migration (Madri et al 1988;Basson et al, 1990;Albelda et al, 1989;Lampugnani et al, 1991). Since significant differences in the monolayer behavior of endothelial cells on the different A375-derived cell lines were observed, we compared the expression of immobilized TN, FN and LN by the A375P, M and SM cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These events appear to be dependent both on cell-cell and cell-matrix interactions. Previous studies have revealed that interaction of endothelial cells with components of extracellular matrix results in modulation of shape and behavior including cytoskeletal reorganization, cell spreading and migration (Madri et al 1988;Basson et al, 1990;Albelda et al, 1989;Lampugnani et al, 1991). Since significant differences in the monolayer behavior of endothelial cells on the different A375-derived cell lines were observed, we compared the expression of immobilized TN, FN and LN by the A375P, M and SM cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the extracellular matrix components of metastatic melanoma appear to correlate with alterations in the adhesion of endothelial cells to these matrices. The interaction of endothelial cells in vitro with components of the extracellular matrix such as laminin (LN), fibronectin (FN), collagen (Col) and proteoglycans (Madri et al, 1980) results in the modulation of shape and behavior of these cells (Madri et al, 1988) resulting in changes which include cytoskeletal reorganization, cell spreading and migration (Basson et al, 1990;Albelda et al, 1989;Lampugnani et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Although many of the mechanisms regulating endothelial cell migration have been defined, those that regulate smooth muscle cell migration are not as well understood. Growth factors such as TGF-f31 (33) and PDGF (34), protease-protease inhibitor cascades (35), extracellular matrix composition (36), cell surface adhesion molecules (37), and hormones (38) regulate endothelial locomotion. Although the same factors appear to regulate smooth muscle cell migration, most of the effects observed are opposite to those seen in endothelial cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…Within the various stages of migration, cell spreading has been shown to correlate more closely with the migration rate than cell attachment (Basson et al, 1990). While cell attachment is likely to be primarily integrin mediated, cell spreading appears to involve nonintegrin matrix-binding proteins as well (Basson et al, 1990). A heterogenous ligand-treated surface, for instance, containing both integrin-dependent adhesion systems and integrin-independent adhesion systems resulted in a significantly higher EC spreading than either of the two systems alone (Bhat et al, 1998).…”
Section: Facilitated Migration: a Key To Spontaneous Endothelializationmentioning
confidence: 99%
“…However, the interplay between attachment and migration demonstrates once more how complex signalling is. Within the various stages of migration, cell spreading has been shown to correlate more closely with the migration rate than cell attachment (Basson et al, 1990). While cell attachment is likely to be primarily integrin mediated, cell spreading appears to involve nonintegrin matrix-binding proteins as well (Basson et al, 1990).…”
Section: Facilitated Migration: a Key To Spontaneous Endothelializationmentioning
confidence: 99%